METHOD OF SURGICAL TREATMENT CENTRAL INTERVERTEBRAL DISC HERNIATION OF THE LUMBAR PART (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction. This article describes a new method for the treatment of central hernias of the lumbar spine in comparison with other methods of anterior and posterior decompression of the dural sac. Indications and contraindications for this method, advantages and disadvantages of existing methods in the treatment of spinal stenosis.